Meta-Analysis: Depression as A Risk Factor for Dementia - Hesthi Krisnawati (Journal of Epidemiology and Public Health, 2022)
Background: Depression is a mental disorder which if not treated can cause other diseases, including the individual's physical condition. One of the risks that occur due to recurrent depression is dementia. Dementia can reduce a person's ability to survive due to decreased brain function. This study was aimed to determine the effect of depression (depression) as a risk factor for dementia (dementia).Subjects and Method: This study was a meta-analysis, with a PICO covering Population= people with dementia. Intervention= depression. Comparison= without depression. Outcome= the risk of dementia. Research data was searched from several sources including: PubMed, Google Scholar, Springer Link, and Science Direct from 2011 until 2021 with the following keywords "dementia" AND "depression" OR "risk of dementia" AND “Hazard Ratio” AND "multivariate". The inclusion criteria used were full papers using English with a cohort study design from 2011-2021 by reporting the Adjusted Hazard Ratio (aHR) value. The selection of articles was carried out using the PRISMA flow diagram. Data processing using Review Manager software version 5.3 to determine the risk of depression variables on dementia.Results: A total of 11 cohort studies were selected for a systematic review and meta-analysis. The data collected showed that depression can increase patients of dementia 1.38 times compared to without depression (aHR= 1.38; 95% CI= 1.38 to 1.70; p=0.003).Conclusion: Depression increases the risk of developing dementia. Keywords: depression, dementia, risk factor. Correspondence:Hesthi Krisnawati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 Kentingan, Jebres, Surakarta, Central Java. Email: hesthikrisna86@gmail.com. Mobile +628527-8067840